Dirk van Hulle. Modern Manuscripts: The Extended Mind and Creative Undoing from Darwin to Beckett and Beyond. London: Bloomsbury, 2014. xiii + 271 pp. - Anna E Hiller (Studies in 20th & 21st Century Literature, 2014)
Review of Dirk van Hulle. Modern Manuscripts: The Extended Mind and Creative Undoing from Darwin to Beckett and Beyond. London: Bloomsbury, 2014. xiii + 271 pp.
Keywords: genetic criticism; modernism; cognitive psychology